Moderasi Beragama dalam Pendidikan Kristiani bagi Generasi Alpha - Merensiana Hale (JURNAL TERUNA BHAKTI, 2022)
The perspective and attitude of religious moderation is a necessity in the context of religious diversity, especially in East Nusa Tenggara (NTT). Religious diversity in NTT is a potential as well as a challenge that needs to be managed properly, especially through Christian education. The Evangelical Christian Church in Timor (GMIT), which is one of the churches in the NTT region, can play a role in supporting religious moderation education, through service to the Alpha generation. This generation is a concern because they were born in the digital era with dominant digital, social, global, mobile, and visual characters. This paper aims to offer a learning model that supports religious moderation for the Alpha generation. The method used is relevant literature research. The results offered are learning models in Christian education to form perspectives and attitudes of religious moderation for the Alpha generation. The models offered are individualized learning models, self-directed learning, collaboration, and inquiry-based learning. AbstrakPerspektif dan sikap moderasi beragama merupakan kebutuhan dalam konteks keberagaman agama, secara khusus di Nusa Tenggara Timur (NTT). Keberagaman agama di NTT merupakan potensi sekaligus tantangan yang perlu dikelola dengan baik, khususnya melalui pendidikan kristiani. Gereja Masehi Injili di Timor (GMIT) yang merupakan salah satu gereja di wilayah NTT dapat berperan mendukung pendidikan moderasi beragama, melalui pelayanan terhadap generasi Alpha. Generasi ini menjadi perhatian sebab mereka lahir di era digital dengan karakter dominan digital, social, global, mobile dan visual. Tulisan ini bertujuan menawarkan model pembelajaran yang mendukung moderasi beragama bagi generasi Alpha. Metode yang digunakan adalah penelitian literatur yang relevan. Hasil yang ditawarkan adalah model pembelajaran dalam pendidikan kristiani untuk membentuk perspektif dan sikap moderasi beragama bagi generasi Alpha. Model yang ditawarkan adalah model pembelajaran individualised, self-directed learning, collaboration, dan inquiry-based learning.